Penjadwalan Flow Shop dengan Metode Algoritma Heuristik Pour, Algoritma Campbell Dudek and Smith, Algoritma Tabu Search di Industri Porcelain Tableware - Edhiargo Toyosito, Rakay; Citra Ramadhanti, Lifia; Yazid Bustommy, Abby (Universitas Tangerang Raya, 2021)
Porcelain tableware industry is an industry that produces household appliances. The production process must be calculated to fulfill the demand with the process. In calculation with pour algorithm method, campbell dudek and smith algorithm and tabu search algorithm by using visual basic for application software so it can speed up the calculations and avoid the errors in calculations. The objective is to minimize the constraint in the production, to fulfill the market demand and produce more quality of A and B. The calculation result of statistical test can use minitab software to find out whether the calculation can be accepted or rejected. Then, these calculation can be executed into the production of porcelain. In this research, production planning can be done by the VBA calculation result which is the campbell dudek and smith algorithm because it produce an optimal makespan compared to the other algorithm results. The comparison result of statistical test is the campbell dudek and smith algorithm produce the smallest p-value than the others. It concludes that the planning of porcelain tableware can use the campbell dudek and smith algorithm in making work sequences to minimize the processing time and have a high quality products.